SIKAP KERJA BERHUBUNGAN DENGAN RISIKO TERJADINYA LOW BACK PAIN PADA TENAGA KESEHATAN GIGI DAN MULUT - Farida, Nurul Indri; Nurnaningsih, Hera; Laut, Deru Marah; Fatikhah, Nurul (Poltekkes Kemenkes Bandung, 2025)
Low Back Pain is the most common health condition in dental health workers that is often reported. Almost every dental health worker in the world has suffered from this problem in his career. This condition is caused by a person's position that is not ergonomic and occurs over a relatively long period of time. This study aimed to determine the relationship between work attitude and the risk of Low Back Pain (LBP) in dental and oral health workers at RSKGM Bandung City. This research was a quantitative research with sampling, namely purposive sample using cross-sectional analytical method located at RSKGM Bandung City. The research data collection was carried out by filling out the Nordic Body Map (NBM) sheet and observing the work attitude of dental and oral health workers with the RULA assessment system. Research data analysis technique using Kendall’s Tau correlation test. From the results of the analysis, a correlation coefficient (R) value of 0.463 was obtained with a strong correlation strength and a p-value of 0.001 < 0.05. The results of the study can be concluded that there was a relationship between work attitude and the risk of Low Back Pain in dental and oral health workers at RSKGM Bandung City.